PENGARUH PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN PT. BANK BTPN SYARIAH TBK CABANG CIBINGBIN KUNINGAN - Vina Andita Pratiwi; Lia Nurliawati (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2020)
This research is motivated by the influence of incentives on financial performance. This study discusses to study and evaluate the provision of incentives to employee performance, in accordance with the established hypothesis that it is suspected that there is a positive and significant influence between providing incentives to employee performance at PT BTPN Syariah Tbk Cibingbin Kuningan Branch. The method used is a quantitative descriptive analysis with the participation of 30 employees. Less than 100 people. Then there is no need for sample calculations. So the respondents in this study were 30 employees.The results of the study concluded that the hypothesis was proven, The results of the hypothesis testing proved to prove between incentives to employee performance through the results obtained a significant level of 0.0000 0.05, which means the hypothesis in this study received H1 means incentives intended for companies.